IMPROVING EARLY CHILDHOOD LANGUAGE SKILLS IN EARLY LITERACY ACTIVITIES THROUGH SAND MEDIA: A COMMUNITY SERVICE PROGRAM AT TK TRISULA I, KEDIRI CITY - Yoyok F.; Aureola C.M.W; Mikielson J; Neza P.N.; Yeti M.R.D.; Jefanto T.A. (Pedagogic Research-Applied Literacy Journal, 2026)
Early literacy development is a fundamental foundation for children’s language acquisition and future academic success. However, learning activities that are monotonous and lack engaging media often reduce children’s motivation and participation in early literacy learning. This community service program aimed to improve the language skills of children aged 5–6 years in early literacy activities using sand as a learning medium at TK Trisula I, Kediri City, during the 2025/2026 academic year. The program employed an intervention-based approach using classroom action cycles consisting of planning, implementation, observation, and reflection. The participants were 12 children from Group B. Data were collected through observation sheets assessing three aspects of language skills: neatness, independence, and accuracy in recognizing and writing letters. The results showed a gradual improvement in children’s language skills across learning cycles. In Cycle I, the average achievement reached 60.42%, categorized as Developing as Expected. The findings indicate that sand media provides a meaningful, enjoyable, and sensory-rich learning experience that supports children’s early literacy development. This program concludes that the use of sand as a learning medium is effective in enhancing early childhood language skills and can serve as an alternative instructional strategy in early childhood education settings.